2015
DOI: 10.1021/jp511156d
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Phosphorus Bonding in Phosphorus Trichloride–Methanol Adduct: A Matrix Isolation Infrared and ab Initio Computational Study

Abstract: The weak interaction between PCl3 and CH3OH was investigated using matrix isolation infrared spectroscopy and ab initio computations. In a nitrogen matrix at low temperature, the noncovalent adduct was generated and characterized using Fourier transform infrared spectroscopy. Computations were performed at B3LYP/6-311++G(d,p), B3LYP/aug-cc-pVDZ, and MP2/6-311++G(d,p) levels of theory to optimize the possible geometries of PCl3-CH3OH adducts. Computations revealed two minima on the potential energy surface, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 101 publications
0
17
0
Order By: Relevance
“…Gas phase reaction of phosphorus trichloride (PCl 3 ) and MeOH was carried out at different ratios of PCl 3 /MeOH and the products were identied using matrix isolation infrared spectroscopy. 21 Infrared vibrational spectra of matrix isolated PCl 3 , MeOH and their complexes were analyzed and assigned by comparing the observed and calculated frequencies and intensities. The experimental evidence for the noncovalent P/O interaction in PCl 3 -MeOH adducts was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Gas phase reaction of phosphorus trichloride (PCl 3 ) and MeOH was carried out at different ratios of PCl 3 /MeOH and the products were identied using matrix isolation infrared spectroscopy. 21 Infrared vibrational spectra of matrix isolated PCl 3 , MeOH and their complexes were analyzed and assigned by comparing the observed and calculated frequencies and intensities. The experimental evidence for the noncovalent P/O interaction in PCl 3 -MeOH adducts was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, these new features are not due to the PCl 3 eCH 3 OH adducts in the N 2 matrix, as the adduct features were characterized in the earlier study [25].…”
Section: Methodsmentioning
confidence: 51%
“…The lone pair of electrons on oxygen of CH 3 OH attacks the electrophilic phosphorus of PCl 3 with a simultaneous cleavage of one of the PeCl bonds and the product DCMP is formed as shown in Fig. 2 3 OH were co-deposited through twin-jet nozzle in a N 2 matrix instead of premixing the gases and then deposited [25]. Recently, extensive [39e43] and named it as pnictogen bonding or more specifically phosphorus bonding.…”
Section: Mechanism Predicted On the Basis Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The B…P bond length was significantly lower than the sum of the van der Waals radii, and the energy value exceeded 10 kcal/mol. In study [24] the presence of a non-covalent O…P bond in the CH 3 -HO…PCl 3 adducts was confirmed using infrared spectroscopy. The formation of a bound adduct was evidenced by displacements of stretching vibrations of the P-Cl, O-C, and O-H bonds into the long-wavelength region.…”
Section: Introductionmentioning
confidence: 88%